Condom catheter induced penile skin erosion. Issue 10 (22nd October 2018) - Sinha, Avinash Kumar; Kumar, Nilay; Kumar, Abhinav; Singh, Saurabh
Abstract: Condom catheters are known to be discrete, reliable, comfortable and very easy to use which makes them preferable to bladder catheter (Saint et al . (Urinary catheters: What type do men and their nursesprefer? J Am Geriatr SOC 1999;47:1453–1457); Hirsh et al . (Do condom catheter collecting systems cause urinary tract infection? J Am Med Assoc 1979;2:0–1)). Condom catheters are widely used in the management of male urinary incontinence, bedridden patient and geriatric population. They are considered to be safe, however, they are associated with complications in care of an incorrect use. In our hospital setup a 73-year-old male bedridden patient attended the surgical opd with complain of penile skin erosion following condom catheter application for 4 days for which dressing was done to remove the slough for 2 days then circumcision was done. Henceforth, although a less known complications are associated with the condom catheter but if not attended promptly can lead to a grave condition like penile gangrene, necrosis, death (Özkan et al. (Penile strangulation and necrosis due to condom catheter. Int Wound J 2015;12:248–9. doi: 10.1111/iwj.12102. Epub 2013 Jun 11); Johnson (The condom catheter: urinary tract infection and other complications. South Med J 1983;76:579–82)).